UPAYA MENGURANGI KOTORAN DAN KANDUNGAN ZAT EKSTRAKTIF SERAT TANDAN KOSONG KELAPA SAWIT DENGAN PENCUCIAN Reduction of Dirts and Extractives Contents of Oil Palm Empty Fruit Bunch Fiber by Water Treatment. - Euis Hermiati; Nurhayati Nurhayati; Lisman Suryanegara; Mohamad Gopar (Jurnal Ilmu dan Teknologi Kayu Tropis, 2003)
The purpose of this study is to get an optimum washing process of oil palm empty fruit bunch (OP EFB) fiber to reduce dirts and extractives contents in the fiber.  Treatments used were boiling (0.5; 1; 2 and 3 hours); soaking and shaking in cold water (1; 4; 8; 12; 24 and 48 hours); 10 minutes agitation in cold water using a washing machine; and 10 minutes agitation in cold water using a washing machine followed by boiling for 0.5 hours.  The clean fiber yield as well as water, ash, hot and cold water soluble extractives and fat contents were determined.  Results of this study showed that soaking and shaking of OP EFB fiber in cold water were quite effective for removing dirts on the fiber, but were not for removing hot and cold water extractives and fats.  Strong agitation could increase the removal of dirts and extractives from the OP EFB fiber.  However, boiling and combination of agitation and boiling removed dirts and extractives more effectively than did the two former processes